The neglected potential of red and processed meat replacement with alternative protein sources: simulation modelling and systematic review. (February 2023) - Reynolds, Andrew N.; Mhurchu, Cliona Ni; Kok, Zi-Yi; Cleghorn, Christine
Summary: Background: What we eat is fundamental to human and planetary health, with the current global dietary transition towards increased red meat intakes and ultra-processed foods likely detrimental. Methods: We modelled five red and processed meat replacement scenarios to consider health, equity, greenhouse gas emissions (GHGe), and cost outcomes using an established multistate life table model using data from New Zealand as a case study of a developed, westernised country. Current red and processed meat intakes were replaced with: minimally or ultra-processed plant based meat alternatives, cellular meat, or diets in line with EAT-Lancet or Heart Foundation recommendations on red meat intake. We then conducted a systematic review of literature from database inception to 14 November 2022 to identify implemented population-level meat replacement strategies which could inform evidence-based recommendations to achieve any benefits observed in modelling. PROSPERO CRD42020200023. Findings: When compared with current red and processed meat intakes, all red and processed meat replacement scenarios were nutritionally adequate and improved overall Quality Adjusted Life Years (159–297 per 1000 people over life course for the five scenarios modelled). Age standardised per capita health gain for Māori was 1.6–2.3 times that of non-Māori. Health system cost savings were $2530–$5096 per adult, and GHGe reduced 19–35%. Finally, grocery cost varied (↓7%–↑2%) per modelled scenario when compared with baseline costs. The greatest benefits for all outcomes were achieved by meat replacement with minimally-processed plant-based foods, such as legumes. The systematic review identified only two implemented population-level strategies to reduce meat intakes within the academic literature. Interpretation: All meat replacement scenarios considered indicated appreciable health gains and GHGe reductions. Replacement with minimally-processed plant-based foods appeared consistently superior than other scenarios. Evidence of real-world population strategies to achieve these benefits however is currently lacking. Funding: Healthier Lives National Science Challenge (Grant UOOX1902 ).